Efficacy of a toothpaste containing paeonol, potassium nitrate, and strontium chloride on dentine hypersensitivity: A double-blind randomized controlled trial in Chinese adults - Jia Li; Qi Han; Li Zhang; Jing Zhang; Yisi Zhong (Heliyon, 2023)
Objective: The purpose of this randomized controlled trial was to compare the efficacy of a toothpaste containing paeonol, potassium nitrate, and strontium chloride with control toothpaste on dentine hypersensitivity (DH). Methods: DH patients who had at least two sensitive teeth and did not use desensitization toothpaste in the past 3 months were randomly allocated to either test or control group. The toothpaste containing paeonol, potassium nitrate, and strontium chloride was used in the test group, while the placebo toothpaste used in control group. The outcome measures included Yeaple probe score and Schiff Index score at 4 and 8 weeks. The patients, personnel and assessors were blinded to the allocation. The differences in Yeaple probe score and Schiff Index score between groups were analyzed with ANOVA. Results: 91 eligible subjects were randomized. 88 of them completed 8-week follow-up and were analyzed (45 in the test group and 43 in the control group). In both groups, the Yeaple probe score showed an upward trend, while the Schiff sensitivity score showed a downward trend. At week 8, the Yeaple probe score had increased by 30.22 g in the test group, and the Schiff Index score had decreased by 0.89. Compared with the control group, the Yeaple probe score in the test group increased by 286.85% from baseline, and the Schiff Index score decreased by 42.96%, showing a statistically significant difference. Five cases of adverse events were observed. Conclusion: The toothpaste containing paeonol, potassium nitrate, and strontium chloride was effective against DH. Clinical significance: This combination of paeonol, potassium nitrate and strontium chloride could be a novel functional ingredient choice for anti-hypersensitivity products in future. Registration: The trial was registered in the Chinese Clinical Trial Registry (ChiCTR2000041417).